Nerve growth factor-induced neurite outgrowth is potentiated by stabilization of TrkA receptors - Song, Eun Joo; Yoo, Young Sook (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2011)
Exogenous stimuli such as nerve growth factor (NGF) exert their effects on neurite outgrowth via Irk neurotrophin receptors. TrkA receptors are known to be ubiquitinated via proteasome inhibition in the presence of NGF. However, the effect of proteasome inhibition on neurite outgrowth has not been studied extensively. To clarify these issues, we investigated signaling events in PC12 cells treated with NGF and the proteasome inhibitor MG132. We found that MG132 facilitated NGF-induced neurite outgrowth and potentiated the phosphorylation of the extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) and phosphatidylinositol-3-kinase (PI3K)/AKT pathways and TrkA receptors. MG132 stimulated internalization of surface Trick receptor and stabilized intracellular TrkA receptor, and the Ub(K63) chain was found to be essential for stability. These results indicate that the ubiquitin-proteasome system potentiated neurite formation by regulating the stability of TrkA receptors. [BMB reports 2011; 44(3): 182-186]
Keywords: P75 NEUROTROPHIN RECEPTOR; PC12 CELLS; SIGNAL-TRANSDUCTION; PROTEASOME; UBIQUITIN; DEGRADATION; INHIBITION; ROLES; INTERNALIZATION; SYSTEM